Café Marketing Strategy Analysis in The Covid-19 Pandemic - Sitorus, Nova Bernedeta; Juliana, Juliana; Maleachi, Sandra; Djakasaputra, Arifin; Prabowo, Gunawan (IJOSMAS, 2021)
Entering the pandemic period, S.T. made several strategic changes. ALi Jakarta includes outlets in SetiaBudi to continue innovating and attracting buyers to shop because of the PSBB and PPKM, which have made profits from the food and beverage industry relatively low. S.T.ALi carried out several marketing strategies during the pandemic. ST, ALi will focus on marketing instant products that are easy to enjoy at home because buyers will spend more time at home. 1-litre bottle packaging and care products are one of the breakthroughs that are widely discussed in Indonesia. This 1-litre bottle packaging can also be more easily marketed with the emergence of new drink types and flavours that are continuously updated regularly within a certain period. In this study, there are two problem formulations: (1) how is the marketing strategy of S.T. Ali Jakarta outlets during the Covid-19 pandemic (2) how does S.T. carry out the marketing mix. Ali outlets during the Covid-19 pandemic. The purpose of this study is to analyze the marketing strategy of S.T. Ali Jakarta outlets during the Covid-19 pandemic and to explore the marketing mix carried out by S.T.ALi outlets during the Covid-19 pandemic. This research is qualitative. The object used in this research is a cafe named S.T. ALi Jakarta, which has an Australian-style concept. Data collection techniques include surveys, participation, observation, interviews, field notes, and analytical memos, elicitation of documents, personal experiences, and participation in follow-up studies. Some data collection techniques are the same as